The Impact of 9/11 and the New Legal Landscape
XV, 284 p.
Keywords: The Impact of 9/11 and the New Legal Landscape is the third volume of the six-volume series The Day that Changed Everything? edited by Matthew J. Morgan. The series brings together from a broad spectrum of disciplines the leading thinkers of our time to reflect on one of the most significant events of our time.